Bright radio emission from an ultraluminous stellar-mass microquasar in M 31 - Middleton, Matthew J.; Miller-Jones, James C. A.; Markoff, Sera; Fender, Rob; Henze, Martin; Hurley-Walker, Natasha; Scaife, Anna M. M.; Roberts, Timothy P.; Walton, Dominic; Carpenter, John; Macquart, Jean-Pierre; Bower, Geoffrey C.; et al. (2013)
A subset of ultraluminous X-ray sources (those with luminosities of less than 1040 erg s-1 ref. 1) are thought to be powered by the accretion of gas onto black holes with masses of ~5-20, probably by means of an accretion disk. The X-ray and radio emission are coupled in such Galactic sources; the radio emission originates in a relativistic jet thought to be launched from the innermost regions near the black hole, with the most powerful emission occurring when the rate of infalling matter approaches a theoretical maximum (the Eddington limit). Only four such maximal sources are known in the Milky Way, and the absorption of soft X-rays in the interstellar medium hinders the determination of the causal sequence of events that leads to the ejection of the jet. Here we report radio and X-ray observations of a bright new X-ray source in the nearby galaxy M 31, whose peak luminosity exceeded 1039 erg s-1. The radio luminosity is extremely high and shows variability on a timescale of tens of minutes, arguing that the source is highly compact and powered by accretion close to the Eddington limit onto a black hole of stellar mass. Continued radio and X-ray monitoring of such sources should reveal the causal relationship between the accretion flow and the powerful jet emission.
Keywords: Astrophysics - High Energy Astrophysical Phenomena